Polymorphic variants of IGF2BP3 and SENCR have an impact on predisposition and/or progression of Ewing sarcoma - Martinelli, Marcella; Mancarella, Caterina; Scapoli, Luca; Palmieri, Annalisa; De Sanctis, Paola; Ferrari, Cristina; Pasello, Michela; Zucchini, Cinzia; Scotlandi, Katia (Frontiers in Oncology, 2022)
Ewing sarcoma (EWS), the second most common malignant bone tumor in children and adolescents, occurs abruptly without clear evidence of tumor history or progression. Previous association studies have identified some inherited variants associated with the risk of developing EWS but a common picture of the germline susceptibility to this tumor remains largely unclear. Here, we examine the association between thirty single nucleotide polymorphisms (SNPs) of the IGF2BP3, a gene that codes for an oncofetal RNA-binding protein demonstrated to be important for EWS patient’s risk stratification, and five SNPs of SENCR, a long non-coding RNA shown to regulate IGF2BP3. An association between polymorphisms and EWS susceptibility was observed for three IGF2BP3 SNPs - rs112316332, rs13242065, rs12700421 - and for four SENCR SNPs - rs10893909, rs11221437, rs12420823, rs4526784 -. In addition, IGF2BP3 rs34033684 and SENCR rs10893909 variants increased the risk for female respect to male subgroup when carried together, while IGF2BP3 rs13242065 or rs76983703 variants reduced the probability of a disease later onset (> 14 years). Moreover, the absence of IGF2BP3 rs10488282 variant and the presence of rs199653 or rs35875486 variant were significantly associated with a worse survival in EWS patients with localized disease at diagnosis. Overall, our data provide the first evidence linking genetic variants of IGF2BP3 and its modulator SENCR to the risk of EWS development and to disease progression, thus supporting the concept that heritable factors can influence susceptibility to EWS and may help to predict patient prognosis.